Pulp calcification in traumatized teeth – a literature review (Research, Society and Development, 2022)
Dental injuries are situations that occur frequently in the population, the prevalence is higher in males, school-age people or athletes. Depending on the severity of the trauma, complications may arise that must be correctly diagnosed and treated. Such complications include pulp necrosis, external or replacement root resorptions, and pulp chamber calcifications. Root canal obliteration or calcifying metamorphosis is characterized by the deposition of hard tissue in the pulp space, which can be seen radiographically, and by the yellowish color of the dental crown. In some cases, it can be associated with pulp necrosis and presence of periapical lesion, and the treatment can be considered complex. Most pulpal calcifications are asymptomatic and are classified according to location and morphology. The main diagnostic method has been through intraoral and panoramic radiographs, although Cone Beam Computed Tomography (CBCT) offers better details. Therefore, the objective of this study was to review the literature on the patterns of pulp calcification most frequently reported in the scientific literature related to dental trauma, in order to help the professional with guidance, diagnosis, treatment planning and proper prognosis.